2007
DOI: 10.1002/jbm.a.31661
|View full text |Cite
|
Sign up to set email alerts
|

Inverse opal hydrogel‐collagen composite scaffolds as a supportive microenvironment for immune cell migration

Abstract: Immunotherapies harness the inherent potential of the body to destroy foreign or infected cells, and are currently being investigated as treatments for cancer. One way to boost native immune responses might be to engineer ectopic lymphoid tissue, providing a supportive microenvironment for immune cell priming, and/or bringing together immune cells at a desired location (e.g., solid tumor sites). Here we describe the development and in vitro testing of composite macroporous poly(ethylene glycol) (PEG) hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 70 publications
2
100
0
Order By: Relevance
“…This provides evidence that encapsulated T cells will retain their potential to kill the CTGel2-neighboring cancer cells of the tumor microenvironment. To date, little progress has been made towards the development of 3D scaffolds for T cell delivery or recruitment for immunotherapeutic strategies [45][46][47][48][49]. Stephan et al have designed an alginate scaffold able to release T cell over time for the treatment of inaccessible tumors or cancer recurrence [45].…”
Section: Antigen-specific Encapsulated T Cells Migrate To and Kill Camentioning
confidence: 99%
See 1 more Smart Citation
“…This provides evidence that encapsulated T cells will retain their potential to kill the CTGel2-neighboring cancer cells of the tumor microenvironment. To date, little progress has been made towards the development of 3D scaffolds for T cell delivery or recruitment for immunotherapeutic strategies [45][46][47][48][49]. Stephan et al have designed an alginate scaffold able to release T cell over time for the treatment of inaccessible tumors or cancer recurrence [45].…”
Section: Antigen-specific Encapsulated T Cells Migrate To and Kill Camentioning
confidence: 99%
“…Stephan et al have designed an alginate scaffold able to release T cell over time for the treatment of inaccessible tumors or cancer recurrence [45]. These scaffolds however, require open surgery for their implantation [45,46]. Moreover, since alginate is not naturally enzymatically degraded in mammals, months may pass before they are completely removed from their original sites of implantation [50].…”
Section: Antigen-specific Encapsulated T Cells Migrate To and Kill Camentioning
confidence: 99%
“…Surface patterning methods have been employed to generate precise domains that bear molecular signals that are normally presented by APCs, such as T cell receptor ligands and ICAM-1, to more precisely understand the interactions between DCs as presenters of those signals and T cells as receivers and explore the regulation of synapse formation between them [84,85]; this is addressed elsewhere in this issue. With regard to generation of engineered lymph node environments for basic immunological investigation, porous materials have been explored as model microenvironments to explore the mechanisms by which DCs present ligands to a large number of T cells within the lymph node microenvironments [86].…”
Section: Lymphatic Tissue Engineeringmentioning
confidence: 99%
“…Biomaterials that release chemoattractants to create de novo chemoattractant gradients and elicit directed cell migration have been demonstrated in vitro and in vivo. [46][47][48][49][50] Alternatively, selective exclusion of inflammatory cells from tissue sites, in some instances, also may be of interest in tissue regeneration to block chronic inflammatory processes and avoid unwanted inflammatory cell accumulation within/around tissue scaffolds. Interestingly, certain proteins can act as chemorepellents, driving immune cell migration away from tissue sites.…”
Section: Controlling Immune Cell Recruitment To Tissue Sitesmentioning
confidence: 99%
“…56,57 Thus, tissue scaffolds decorated with heparan sulfate proteoglycans or heparin can be loaded with chemoattractants by physisorption for slow release and gradient generation. 48 Finally, vaccine studies have convincingly demonstrated the utility of plasmid DNA inoculation to locally transfect tissue cells to produce chemoattractants that draw immune cells to an injection site, 58,59 and materials designed to promote plasmid delivery could likewise be tailored to this purpose in the setting of tissue regeneration.…”
Section: Controlling Immune Cell Recruitment To Tissue Sitesmentioning
confidence: 99%